The economic valuation of marine ecosystems - Paulo A. L. D. Nunes; Helen Ding; Anil Markandya (Fondazione Eni Enrico Mattei (FEEM), 2009)
In a democratic system, policy makers have to take the preferences of the citizens into account. Since we live in a world with scarce resources, one is asked to make choices regarding the use and management of these resources. In this context, if policy makers decide to invest in the protection of marine ecosystems, less financial resources will be available for other policy areas, for example national health. Moreover, the investment in the protection of marine ecosystems brings along with it the provision of a wide range of benefits to humans though most are not priced in the existing markets - for example climate regulation and provision of habitat for biodiversity. Given that most human activities are priced in one way or other, in some decision contexts, the temptation exists to downplay or ignore these important marine ecosystem benefits on the basis of the non-existence of prices. The simple and simplistic idea in the minds of many policymakers is that a lack of prices is equivalent to a lack of values. Clearly, this is a biased perspective. Against this background, this paper explores the motivation for an economic valuation of this complex resource. The state-of-the-art economic valuation methodologies follow the guidelines proposed by the Millennium Ecosystem Assessment, taking into account the existing scientific knowledge on the functioning of marine ecosystems, marine ecosystem goods and services and its impacts on human welfare. Finally, we critically review some economic valuation studies, arguing that the economic valuation of marine ecosystem services and biodiversity can make sense if and only if important guidelines are observed.
Keywords: Q50; Q57; 330; Economic Valuation; Marine Ecosystem; Millennium Ecosystem Assessment Approach; Europe